Women who expose vulnerabilities generated by hy-drocarbon activity in Norpatagonia (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
In the last decade the Vaca Muerta area has been renowned, as a logistics epicenter in Añelo that is located 100 kms from Neuquén Capital. The volume of gas and oil reservoirs in the area puts feminist studies in the region on alert regarding the segregations that activity entails in the bodies of women who are directly affected by the impacts of hydrocarbon activity. In this sense, it is intended to make visible the claims that they carry out and account for some conditions.This paper aims to analyze certain disagreements between the productivist notion of business development that concentrates the extraction of hydrocarbons and the social demands around better conditions of urbanity or transfer in Añelo. There are poor living conditions, ignorance of pre-existing indigenous peoples and few environmental precautions.
Keywords: Vaca Muerta; Women; Claims; care tasks